Silicon carbide nanotubes (SiCNTs) serving for catalytic decomposition of toxic diazomethane (DAZM) gas: a DFT study. (1st February 2018) - Solimannejad, Mohammad; Kamalinahad, Saeedeh; Shakerzadeh, Ehsan
ABSTRACT: In the present study, the adsorption and decomposition of diazomethane (DAZM) on the surface of (6, 0) zigzag silicon carbide nanotube (SiCNT) are investigated using density functional theory calculations. The geometry structures of the three stable configurations, adsorption energies and electronic properties of DAZM adsorption on the surface of SiCNT are investigated. It was found that the DAZM molecule is decomposed over the surface of (6, 0) SiCNT with activation energy ( E act ) of 0.523 eV. The curvature effect on the adsorption energies of the DAZM molecule is also considered by studying (5, 0) and (7, 0) SiCNTs. The results display that DAZM adsorption over smaller diameter of SiCNT is thermodynamically more favourable than larger one. Abstract :